2003
DOI: 10.1262/jrd.49.539
|View full text |Cite
|
Sign up to set email alerts
|

Effects of In Utero Exposure to Bisphenol A on Expression of RAR.ALPHA. and RXR.ALPHA. mRNAs in Murine Embryos

Abstract: Abstract. Retinoic acid receptor (RAR) α and retinoid X receptor (RXR) α are key factors in a nuclear receptor-dependent signal. To evaluate the effects of bisphenol A (BPA), a candidate endocrine disruptor (ED), on embryonic development, we examined the mRNA levels of RARα and RXRα in murine embryos, exposed in utero to BPA (2 µg/kg/day) at 6.5-17.5 days post-coitum (dpc), by the realtime reverse transcription-polymerase chain reaction (RT-PCR) method. Higher levels of RARα mRNA in cerebra of male and female … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 31 publications
1
23
0
Order By: Relevance
“…Nishizawa et al (2003), supported by the Japanese Ministry of Education, Culture, Sports, Science, and Technology, examined the effects of prenatal bisphenol A exposure on expression of retinoic acid receptor a and retinoid X receptor a in mouse embryos. ICR mice were fed standard feed (CM; Oriental Yeast).…”
Section: [No Additional Information Was Provided For Statistical Analmentioning
confidence: 99%
See 2 more Smart Citations
“…Nishizawa et al (2003), supported by the Japanese Ministry of Education, Culture, Sports, Science, and Technology, examined the effects of prenatal bisphenol A exposure on expression of retinoic acid receptor a and retinoid X receptor a in mouse embryos. ICR mice were fed standard feed (CM; Oriental Yeast).…”
Section: [No Additional Information Was Provided For Statistical Analmentioning
confidence: 99%
“…Variable changes in retinoic acid retinoid X receptors á mRNA expression in brain, ovary, and testis, depending on brain region and day of exposure Nishizawa et al (2003) Other Prepubertal Poll Dorset female lambs (i.m. injection) 3.5 biweekly, at 4-11 weeks of age (ovariectomy at 9 weeks of age)…”
Section: Days Postcoitummentioning
confidence: 99%
See 1 more Smart Citation
“…We observed that Cln2 gene promoter lacked the PPAR-binding site but contained an RXR-binding site instead. Because of the facts that RXR␣ is abundant in the brain and astrocytes (32,33) and that PPAR␣ and RXR␣ form a heterodimer, we thought the mechanism of up-regulation of TPP1 may involve cooperative action of both PPAR␣ and RXR␣ and not PPAR␣ alone. To verify our hypothesis, we performed an array of experiments.…”
Section: Up-regulation Of Tpp1 By Fibrate Drugs Involves Both Ppar␣mentioning
confidence: 99%
“…51 Hormones are known regulators of transcription through their effect on DNA methylation and chromatin composition. 52,53 Since EDs can affect DNA methylation patterns 33,54,55 and gene expression, [56][57][58][59][60] it is hypothesized that these hormonelike chemicals can alter the reciprocal epigenetic states of the two parental chromosomes at imprinted genes or their DMRs and those epigenetic changes would alter the allele-specific expression in the embryonic or extraembryonic organs. To test this hypothesis we generated multiplex allele-specific assays and measured the effects of BPA, VZ and DEHP on the maintenance of imprinted gene expression of a representative set of imprinted transcripts in the embryo and in extraembryonic organs after in utero exposure to these chemicals.…”
Section: Effects Of Endocrine Disruptors On Imprinted Gene Expressionmentioning
confidence: 99%